2021
DOI: 10.1108/jaoc-10-2019-0111
|View full text |Cite
|
Sign up to set email alerts
|

Resilience capacities and management control systems in public sector organisations

Abstract: Purpose Inspite of the attention resilience receives in relation to public policy and public management, very few studies have analysed the internal mechanics of public sector organisations to see what is producing their resilience. Considering management control systems (MCSs) as the drivers of organisational change, this paper aims to explore their role as determinants of resilience in the public sector. The paper attempts to open the black box of organisational functioning focusing on one complex component.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
15
0
6

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 72 publications
3
15
0
6
Order By: Relevance
“…Primeiro, evidências já sugerem que sistemas de controle gerencial (SCG) habilitantes fomentam a criação de resiliência cognitiva, comportamental e contextual (Beuren & Santos, 2019) e resiliência organizacional em sentido amplo (Beuren et al, 2020). Sistemas de controle voltados para planejamento, monitoramento, orçamento flexível e gestão de desempenho também auxiliam no desenvolvimento de capacidades de resiliência organizacional (Bracci & Tallaki, 2021). Contudo, para a discussão de mecanismos de controle formais e informais, os achados são menos conclusivos.…”
Section: Introductionunclassified
“…Primeiro, evidências já sugerem que sistemas de controle gerencial (SCG) habilitantes fomentam a criação de resiliência cognitiva, comportamental e contextual (Beuren & Santos, 2019) e resiliência organizacional em sentido amplo (Beuren et al, 2020). Sistemas de controle voltados para planejamento, monitoramento, orçamento flexível e gestão de desempenho também auxiliam no desenvolvimento de capacidades de resiliência organizacional (Bracci & Tallaki, 2021). Contudo, para a discussão de mecanismos de controle formais e informais, os achados são menos conclusivos.…”
Section: Introductionunclassified
“…The tendency to withstand shocks without changing structure or function, the ability to make incremental changes to the existing function and structure without changing underlying principles, culture, or beliefs, and the capacity to manage, absorb, and react to shocks are all examples of coping capacities that become visible through coping actions during times of disruption. The interaction of ecological elements and structural supports throughout time results in coping capacities (Bracci and Tallaki, 2021).…”
Section: Anticipitory Strategiesmentioning
confidence: 99%
“…Aziah and Scapens (2007) found that the implementation of accounting control systems affects the relationship between low-level management and accountancy executives in the Malaysian public sector, based on trust between the two parties. Bracci and Tallaki (2021) suggested that management control systems can assist in the decision-making process and support adaptive behaviour by providing information to cope with external barriers in the public sector. Moreover, Siddiquee (2010) revealed that public services in Malaysia had followed the global trends to implement result control but mentioned that while the current approach tended to suffer from serious inadequacies and limitations, many of the shortcomings of the traditional method could be resolved through result control and budgeting.…”
Section: Employee Organisational Commitment In the Public Sectormentioning
confidence: 99%